The Relevance of Non-litigation Mediation in Family Dispute Resolution to Family Law Reform in Indonesia - ., Nurnazli; Awaludin, Robi; Dewi, Asmara; Akmansyah, Muhammad (KnE Social Sciences, 2024)
Non-litigation mediation is very important for its application in Indonesian society, given the increasing number of cases of family disputes in religious courts. The research question in this study is to what extent extrajudicial mediation is relevant to family law reform in Indonesia, especially in the case of domestic disputes. The approaches used in this study are legal, normative, and philosophical. The main legal materials were based on the Quran, Hadith, and Laws and Regulations. Data processing was done by creating and organizing data. This was a qualitative analysis, with a focus on non-litigation mediation. The findings show that non-litigation mediation in family disputes has been long established in Indonesian society. Non-litigation mediation for resolving family disputes is very important to include in Indonesia’s legal reform agenda. This is because it has a deep connection with Indonesian society. The values of consensus consultation, fraternity, solidarity, mutual cooperation, and tolerance have always been at the forefront of the community in overcoming the various problems that arise and are an advantage in restructuring the rules of non-litigation mediation. However, their implementation is still not optimal. Non-litigation mediation occupies a very powerful position and is rooted in the legal order of life of the Indonesian people, but its application in resolving family disputes is simply underutilized. And community culture. Keywords: Non-litigation mediation, family dispute resolution, family law reform